Penggunaan Strategi Pembelajaran Berbasis Literasi Kritis untuk Meningkatkan Kapasitas Berpikir Reflektif Pada Peserta Didik di SMA - Herdianto, Herdianto (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study examines the implementation of a learning strategy based on critical literacy as an effort to enhance students' reflective thinking skills at SMA Negeri 1 Junjung Sirih. The main issue addressed is the low ability of students to perform reflection, analysis, and understanding of learning material. The purpose of this study is to evaluate how the critical literacy strategy is applied in the learning process and to assess its effects on the development of students' reflective thinking abilities. This study employs a qualitative descriptive approach. The research subjects include teachers who implement the critical literacy strategy and students. Data collection was carried out through participatory observation and semi-structured interviews. The data analysis was conducted qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The research results indicate that a literacy-based learning strategy is effective in increasing student engagement, encouraging deeper information analysis, and stimulating their ability to reflect, express opinions, and evaluate ideas. Although there are some obstacles, such as differences in students' initial literacy skills and limited learning time, overall this strategy has a significant positive impact on strengthening reflective thinking capacity among students.